1975
DOI: 10.2134/jeq1975.00472425000400040008x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ozone on the Yield and Plant Biomass of a Commercial Variety of Tomato

Abstract: A commercial variety of pole tomato (Lycopersicon esculentum Mill. H-11) was exposed to 20 and 35 parts per hundred million (pphm) ozone for 2.5 hours, 3 days each week over a period of weeks. Extensive foliar injury, defoliation, and highly significant reductions in plant biomass occurred at both exposure levels. However, fruit yield was significantly reduced only at the higher 35 pphm ozone concentration. This reduction was due to a decrease in the number of fruit and not to a decrease in fruit weight. Fruit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1978
1978
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Our meta‐analysis and other literature suggests that an increase in flower abortion at elevated [O 3 ] may be dose‐dependent and/or species dependent. For example, flower number was decreased in carnation (Feder & Campbell, ; Feder, ), Lemna perpusilla (Feder & Sullivan, 1969b), Brassica napus (Black et al ., ), Citrillus lanatus and Cucumis melo (Fernandez‐Bayon et al ., ) under elevated [O 3 ], whereas studies done on Lycopersicon esculentum (Oshima et al ., ), Plantago major (Reiling & Davison, ), Phaseolus vulgaris (Kohut et al ., ) and Prunus salicina (Retzlaff et al ., ) all reported an increase in flower number under elevated [O 3 ]. Certainly, more studies of the effects of elevated [O 3 ] on flower initiation and abortion are needed to understand the mechanisms by which O 3 alters flower development.…”
Section: Discussionmentioning
confidence: 99%
“…Our meta‐analysis and other literature suggests that an increase in flower abortion at elevated [O 3 ] may be dose‐dependent and/or species dependent. For example, flower number was decreased in carnation (Feder & Campbell, ; Feder, ), Lemna perpusilla (Feder & Sullivan, 1969b), Brassica napus (Black et al ., ), Citrillus lanatus and Cucumis melo (Fernandez‐Bayon et al ., ) under elevated [O 3 ], whereas studies done on Lycopersicon esculentum (Oshima et al ., ), Plantago major (Reiling & Davison, ), Phaseolus vulgaris (Kohut et al ., ) and Prunus salicina (Retzlaff et al ., ) all reported an increase in flower number under elevated [O 3 ]. Certainly, more studies of the effects of elevated [O 3 ] on flower initiation and abortion are needed to understand the mechanisms by which O 3 alters flower development.…”
Section: Discussionmentioning
confidence: 99%
“…Plants exposed to O 3 at flowering had a significant linear decrease (P < 0.01) in fruit fresh weight with increasing O 3 , while the response for the vegetative stage plants was not significant. Oshima et al (1975) found no significant difference in number of fruits between tomato plants receiving 0.00 or 0.20 µl O 3 /liter for a total of 97 hr during the growth period. However, 0.35 µl O 3 /liter for the same duration led to a reduction in the number of fruits per plant.…”
Section: Experiments Were Conducted In 1985 Andmentioning
confidence: 67%
“…Their findings and ours suggest that there may be a tolerance level that must be exceeded before the number of tomato fruit is reduced. Reduction in tomato fruit fresh weight caused by O 3 is well-documented (MacLean and Schneider, 1976;Oshima et al, 1975;Oshima et al, 1977b), but information is limited on tomato response to O 3 in terms of fresh fruit yield after exposure to O 3 at different developmental stages. Plants exposed to O 3 up to 84 days after transplanting showed no yield effect, but at ages greater than this a cumulative yield decline was obtained (MacLean and Schneider, 1976).…”
Section: Experiments Were Conducted In 1985 Andmentioning
confidence: 99%
“…There is no evidence that microsporophytic development is hampered by the presence in the atmosphere of a pollutant like ozone, but there is good evidence that at high levels of ozone, pollen germination is inhibited or prevented, and at lower ozone concentrations pollen tube elongation is markedly inhibited (52,53). These data coupled with other data (54)(55)(56)(57)(58)(59)(60) relating to the depression of fruit yield in many commercial crop plants after exposure to ozone, sulfur dioxide or hydrogen fluoride would appear to implicate the plant reproductive system as a possible target for pollutants. The effects of pollutants on plant growth and development coupled with their effect on plant reproductive system would seem to be best reflected in yield, measured in terms of fruit set, fruit numbers, and fruit size.…”
Section: Pollutant-incited Injurymentioning
confidence: 83%